The Effectiveness of Visualization of Proofs in Learning Mathematics by Using Discovery Learning Viewed from Conceptual Understanding - Angga Kristiyajati; Ariyadi Wijaya (SEAMEO Regional Centre for QITEP in Mathematics, 2019)
The purpose of this study is to explore the effectiveness of the use of visualization of proofs upon discovery learning models in mathematics learning in terms of understanding concepts. This study is an experimental design which used quantitative methods to obtain data on student conceptual understanding. The sampling technique used was stratified random sampling. The population sample used in this study was 11th grade secondary students, chosen from 11 IPA 2 of SMAN 8 Yogyakarta, 11 IPA 3 of SMAN 8 Yogyakarta, 11 IPA 3 of SMAN 2 Yogyakarta, 11 IPA 4 of SMAN 2 Yogyakarta, 11 IPA 1 of SMAN 11 Yogyakarta, and 11 IPA 2 of SMAN 11 Yogyakarta. In each school, two classes were chosen with one class was given a discovery learning treatment with visualization of proofs (PWW) and the other class was given a discovery learning treatment without visualization of proofs. The measurement instrument used in this study was an essay test instrument with five questions. Discovery learning is said to be effective if the average value of conceptual understanding is at least 75. Based on the results of this study, although the data obtained did not meet the assumptions of normality, the number of members of the sample were more than 30 so that the data analysis could use parametric statistics. Using a hypothesis testing with a significance level of 0.05, it was found that the use of visualization of proofs was effective in mathematics discovery learning models if it was viewed from conceptual understanding.